KOMODIFIKASI FILM CRITICAL ELEVEN: Studi Deskriptif Tentang Komodifikasi Ekonomi Politik Film Critical Eleven - Rengga Andhita, Pundra (CV. Amerta Media, 2018)
As technology advances, film is packaged not only as entertainment. Inevitably, the film has become a commodity of the media industry. The existence of film as one medium of communication can be an effective channel for people to consume the message content in accordance with the will of the maker. Currently very easy to find various films that presents the diversity of themes with stories that attract the attention of the public. One of them is the movie